Kalalah Inheritance in QS. al-Nisa [4]: 176: A Comparative Study of the Interpretation of Ibn al-'Arabi and Wahbah az-Zuhaili - Tanti Rostiana Herdiani; Jaka Ghianovan; Khoirun Nidhom (Jurnal Semiotika Quran, 2024)
This article explains the differences between kalalah inheritance from the perspective of Tafsir Ahkam al-Qur'an by Ibn al-'Arabi and Tafsir al-Munir by Wahbah az-Zuhaili as stated in the QS. al-Nisa [4]: ​​176. Using descriptive-comparative qualitative methods, the results of this article explain that the Kalalah heritage is seen from the perspective of Ibn al-'Arabi in Ahkam al-Qur'an and Wahbah az-Zuhaili in Tafsir al- Munir is different in presenting his interpretation. Ibn al-'Arabi understands kalalah as a person who does not leave behind father or child so that the distribution of inheritance follows according to the provisions of the Qur'an and hadith and emphasizes the importance of ijtihad. Meanwhile, according to Wahbah az-Zuhaili in Tafsir al-Munir, kalalah inheritance is understood by people who does not leave father or child so that the distribution of inheritance is determined in three parts, namely for brothers and sisters (co-parents) left behind by the heir, or more sisters left behind by the heir, and the portion of brothers and sisters (co-fathers) who left by the heirs in large amounts. The different interpretations of inheritance of kalalah according to these two commentators show how Islamic law has been understood and applied from different perspectives according to the context of the times and the needs of society. This article shows that Ibn al-'Arabi's interpretation is more classical and textual, while az-Zuhaili's is more flexible and contextual.